2017
DOI: 10.1111/tbj.12862
|View full text |Cite
|
Sign up to set email alerts
|

Management of side effects during and post-treatment in breast cancer survivors

Abstract: Cancer-related fatigue, insomnia, and cancer-related cognitive impairment are commonly experienced symptoms that share psychological and physical manifestations. One or more of these symptoms will affect nearly all patients at some point during their course of treatment or survivorship. These side effects are burdensome and reduce patients' quality of life well beyond their cancer diagnosis and associated care treatments. Cancer-related fatigue, insomnia, and cancer-related cognitive impairment are likely to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 118 publications
2
78
0
3
Order By: Relevance
“…Our findings revealed that PSQI Daytime Dysfunction, PSQI Efficiency, and PSQI Disturbance were the strongest predictors of FACT‐Cog PCI and are consistent with other studies linking sleep disturbance and daytime sleepiness to perceived attention ( rs = 0.32 to −0.64), and self‐reported sleep quality and daytime dysfunction, to PCI in BCS. Similarly, our findings support links between fatigue, a concept related to daytime functioning, and PCI that have been found in BCS . Additionally, significant relationship has been found between subjective sleep quality, daytime sleepiness, and cognitive complaints in older adults .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings revealed that PSQI Daytime Dysfunction, PSQI Efficiency, and PSQI Disturbance were the strongest predictors of FACT‐Cog PCI and are consistent with other studies linking sleep disturbance and daytime sleepiness to perceived attention ( rs = 0.32 to −0.64), and self‐reported sleep quality and daytime dysfunction, to PCI in BCS. Similarly, our findings support links between fatigue, a concept related to daytime functioning, and PCI that have been found in BCS . Additionally, significant relationship has been found between subjective sleep quality, daytime sleepiness, and cognitive complaints in older adults .…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, our findings support links between fatigue, a concept related to daytime functioning, and PCI that have been found in BCS. 37 Additionally, significant relationship has been found between subjective sleep quality, daytime sleepiness, and cognitive complaints in older adults. 35…”
Section: Post Hoc Analysesmentioning
confidence: 99%
“…We did find that being more physically active did reduce symptoms and improve well‐being. Lifestyle interventions, including exercise, reductions in sedentary time, yoga, cognitive retraining, and weight loss, have been shown to increase well‐being in other studies, so this remains an important topic for survivorship care visits …”
Section: Discussionmentioning
confidence: 99%
“…With over 252,000 new breast cancer cases estimated in 2017 and a 90% five-year survival rate, the population of over 3.5 million U.S. breast cancer survivors (BCS) will continue to increase [ 1 , 2 ]. BCS live with many treatment-related side effects including cognitive dysfunction [ 3 ]. There is evidence that up to 75% of breast cancer patients experience cognitive decline during cancer treatment and that these impairments can persist up to twenty years following treatment completion [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%